Large Grained Perovskite Solar Cells Derived from Single-Crystal Perovskite Powders with Enhanced Ambient Stability - Yen, Hung-Ju; Liang, Po-Wei; Chueh, Chu-Chen; Yang, Zhibin; Jen, Alex K.-Y; Wang, Hsing-Lin (ACS applied materials & interfaces, 2016)
In this study, we demonstrate the large grained perovskite solar cells prepared from precursor solution comprising single-crystal perovskite powders for the first time. The resultant large grained perovskite thin film possesses a negligible physical (structural) gap between each large grain and is highly crystalline as evidenced by its fan-shaped birefringence observed under polarized light, which is very different from the thin film prepared from the typical precursor route (MAI + PbI2).